2014
DOI: 10.1016/j.cplett.2014.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen in Cu(1 1 0) surface restructuring in the vicinity of step edges

Abstract: Surface steps are typically assumed as a source of adatoms for oxygen-chemisorption induced surface reconstruction, but few microscopic observations have been made in the vicinity of steps on reconstructing surfaces. Using in-situ scanning tunneling microscopy, we provide direct evidence that surface steps are the source of Cu adatoms for the Cu(110)-(21)-O restructuring. Using density functional theory, we show that the role of oxygen is to stabilize Cu adatoms detached from step edges via the barrier-less f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…The chains start forming above 70 K but do not fully organize until ∼ 200 K 162 . They are formed from mobile chemisorbed O atoms and Cu adatoms which leave from step edges and diffuse across the terraces 138,162,[174][175][176][177][178] . The experimental barrier calculated for the formation of these strings, 0.22±0.01 eV 179 , is close to the DFT-calculated barriers for Cu (0.25 eV) and O (0.15 eV) diffusion 180 .…”
Section: Cu(110)mentioning
confidence: 99%
“…The chains start forming above 70 K but do not fully organize until ∼ 200 K 162 . They are formed from mobile chemisorbed O atoms and Cu adatoms which leave from step edges and diffuse across the terraces 138,162,[174][175][176][177][178] . The experimental barrier calculated for the formation of these strings, 0.22±0.01 eV 179 , is close to the DFT-calculated barriers for Cu (0.25 eV) and O (0.15 eV) diffusion 180 .…”
Section: Cu(110)mentioning
confidence: 99%
“…An estimated 137 quadrillion (10 15 ) Joule of energy are lost yearly due to high-temperature corrosion problems 6 . Although the oxidation reaction of metal surfaces is highly complicated, different elementary processes, many of which are coupled, are involved from the onset of reaction.One good example for the metal oxidation study is the low-miller index surfaces of copper [7][8][9][10][11][12][13] . Recent studies using modern electron microscopy (EM) have revealed that the initial stages of Cu oxidation bear a striking resemblance to heteroepitaxial film growth where interfacial strain is the key factor in thin film growth and determines the shape of the oxide nano-island [14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…Steps are assumed to be the source of Cu adatoms for the oxygen-chemisorption induced (2 × 1) phase formation. [20][21][22] Cu-O chain formation was the mechanism by which atomic oxygen was able to combine with Cu adatoms detaching from step edges and diffusing on the surface. Other experiments found that the ejection of Cu atoms from terraces was also a route for Cu adatom formation.…”
mentioning
confidence: 99%